The potential impact of exercise on affect and neuroinflammation in older adults living with fibromyalgia: a scoping review - Taylor, Taylor L.; Dodds, Fitzgerald; Tharpe, McKenna; Zumbro, Emily L.; Hankes, Michael; Jones, Raymond; Rumble, Deanna; Antoine, Lisa; Allen-Watts, Kristen; Sims, Andrew; Chandra, Reshu; Goodin, Burel R.; et al. (Frontiers in Human Neuroscience, 2025)
IntroductionFibromyalgia (FM) is a widespread chronic pain condition with prevalence increasing in older adults. Older adults living with FM experience longer pain symptom durations that can negatively impact their quality of life. Affect and neuroinflammation are potential factors that can exacerbate pain symptoms. Exercise is a recommended intervention to manage pain symptoms; however, adherence limitations persist. Drawing on the Biopsychosocial Framework of Chronic Pain, this scoping review explores how exercise impacts factors related to neuroinflammation and affect, and how these factors contribute to exercise adherence in older adults living with FM.MethodsWe conducted a scoping search of articles related to exercise and older adults living with FM published before 2024. The extracted study characteristics include publication type, study design, affect outcomes, neuroinflammation outcomes, exercise type, exercise adherence, and sample demographic information.ResultsWe have provided an overview of the relationship between affect and neuroinflammation in studies including older adults living with FM and highlight the impact of exercise on affect and neuroinflammation in older adults living with FM. A conceptual framework is provided illustrating the reciprocal relationship between exercise, affective changes, neuroinflammation, and exercise adherence.DiscussionOur results suggest that exercise may improve affect, while limited evidence suggests that aerobic and resistance exercise improve neuroinflammation. Finally, implications for importance and future directions in the context of potential biological factors impacted are provided.